Philosophy of Emancipatory Education through the Masters of Suspicion - John Christianto Simon; I Gusti Nyoman Arnawa (Jurnal Filsafat "WISDOM", 2023)
This paper will answer what the masters of suspicion say about the construction of today’s relevant philosophy of education. This paper is a qualitative research intended to construct meaning through a literature search on selected reading sources. The hermeneutic perspective used in this paper means an attempt to put the text, namely the thoughts of these masters of suspicion, in the present context to construct a meaning for the relevant philosophy of education. Three masters of suspicion, i.e. Marx, Freud, and Nietzsche, spoke respectively of a critical task in the realm of human action. Marx suspected that economic motives are often not to support life but to suppress it instead. Nietzsche suspected that religion only produced decadent and timid humans so they never became their true selves, hypocrite, and like to scare others. Freud was suspicious of human subconscious motivation so it must be seriously criticized in order to bring out an action that is truly born of compassionate political and social morality. These three masters present important education values to be developed today, namely education for social change, empowerment, and building compassionate social and political morality.